[PR]A.S.S.I. Apprendere serve, servire insegna: a project of Service Learning - Alessandra La Marca; Federica Martino (Firenze University Press, 2023)
Integrating Service Learning (SL) activities into academic courses can offer a transformative experience for students. In the twofold perspective of countering the learning loss, determined by the pandemic, and promoting student empowerment, enhancing responsible learning and self-regulating skills, a Service Learning project was implemented. The project started with a sample of 38 students enrolled in the first year of the Master's Degree in Primary Education at the University of Palermo. To monitor the performance of the SL project, to measure the civic-social competences, self-efficacy and trait anxiety of university students, it was decided to administer a pre and a post of the CUCOCSA Questionnaire. This contribution shows how students acquired reflective, relational and research skills as well as civic-social and metacognitive attitudes.   [PR]A.S.S.I. Apprendere serve, servire insegna: un progetto di Service Learning. Integrare attività di Service Learning (SL) nei corsi accademici può offrire un'esperienza trasformativa per gli studenti. Nella duplice ottica di contrastare il learning loss, determinato dalla pandemia, e di promuovere lo student empowerment, valorizzando l'apprendimento responsabile e le competenze di autoregolazione, è stato realizzato un progetto di Service Learning. Il progetto è stato avviato con un campione di 38 studenti iscritti al primo anno del Corso di Laurea Magistrale in Scienze della Formazione Primaria dell'Università di Palermo. Per monitorare la performance del progetto di SL, per misurare le competenze civico-sociali, l'auto-efficacia e l'ansia di tratto degli studenti universitari, si è deciso di somministrare un pre e un post del Questionario CUCOCSA. In questo contributo si evidenzia come gli studenti hanno acquisito competenze riflessive, relazionali, di ricerca e atteggiamenti civico-sociali e metacognitivi.